Trajectories of agricultural modernization and rural resilience: some first insights derived from case studies in 14 countries - Knickel, Karlheinz (Applied Studies in Agribusiness and Commerce, 2016)
In this paper, alternative trajectories of agricultural modernization and rural resilience are explored based on case studies in 14 countries. The analysis is to support discussions about the further development of agriculture at a time when the agricultural sector must respond to an increasing scarcity of natural resources, challenges like climate change, urbanization, demographic change, food security, consumer demands, distributional issues in food value chains and changing urban-rural relations. The discussion relates different trajectories of agricultural modernization to the multiple mechanisms underlying rural prosperity and resilience. The mainstream capital-intensive and technology-driven model of agricultural modernization is contrasted with more incremental, socially embedded and localised forms of development. Potential synergies between different modes of farm ‘modernization’, resilience and sustainable rural development are highlighted and a different future-oriented understanding of the term ‘modernization’ explored. The basis for the analysis are case studies in 14 countries (including Turkey and Israel). The key question asked is how actors are connecting economic, social and natural systems in the different cases and how the connections made (or not) point to different ideas about modernization. The conclusions focus on some current information needs of policy-makers: the links between different forms of farm modernization, rural development and resilience, and the implications for agricultural knowledge systems and the new European Innovation Partnerships. It is emphasized that local capacities for transdisciplinary research need to be strengthened and that more attention should be paid to addressing modernization potentials that are less mainstream. The paper seeks to foster discussions that help overcome simplistic viewpoints of what ‘modernization’ entails. It is based on an earlier review paper by Knickel, Zemeckis and Tisenkopfs (2014).